2017
DOI: 10.1161/circulationaha.116.026252
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Cardiovascular Health, Compression of Morbidity, and Healthcare Costs

Abstract: Background We examined the association of cardiovascular (CV) health at younger ages with the proportion of life lived free of morbidity, the cumulative burden of morbidity, and average healthcare costs at older ages. Methods The Chicago Heart Association (CHA) study is a longitudinal cohort of employed men and women aged 18–74 years at baseline examination in 1967–1973. Baseline measurements included blood pressure, cholesterol, diabetes, BMI and smoking. Individuals were classified into one of four strata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Overall, those CHA cohort members who had a favorable health profile in midlife had prolonged survival by ≈4 years and postponed onset of all-cause and cardiovascular mortality of 7 years. 173 In addition, all morbidities were reduced, compression of morbidity was observed both absolutely and relatively, and there were lower cumulative and annual healthcare costs during the Medicare-eligibility life span in older ages for those with favorable cardiovascular health profiles in midlife. 173 Although cognition was not the primary focus of this publication, several other study results support the belief that favorable cardiovascular health earlier in life leads to maintenance of cognitive vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, those CHA cohort members who had a favorable health profile in midlife had prolonged survival by ≈4 years and postponed onset of all-cause and cardiovascular mortality of 7 years. 173 In addition, all morbidities were reduced, compression of morbidity was observed both absolutely and relatively, and there were lower cumulative and annual healthcare costs during the Medicare-eligibility life span in older ages for those with favorable cardiovascular health profiles in midlife. 173 Although cognition was not the primary focus of this publication, several other study results support the belief that favorable cardiovascular health earlier in life leads to maintenance of cognitive vitality.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of prospective studies have demonstrated that the presence of ideal CVH metrics at younger age is associated with lower risk of all-cause mortality [ 5 ], lowest rate of functional disability [ 6 ], and reduced health costs [ 7 , 8 ] at older age. Findings from the Hispanic Community Healthy Study/Study of Latinos (HCHS/SOL) showed that the proportion of Hispanics/Latinos with ideal CVH is low (less than 1% have all 7 ideal metrics) and varies by sex with females having more favorable profiles than males [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poorly performing calibration factors (low sensitivity for atherosclerosis and outcome) will unnecessarily delay timely preventive interventions, for instance with statins. This will lead to a substantial increase in long-term morbidity and all-cause mortality as has recently been shown for the principle of compression of morbidity in the Chicago area (Allen et al, 2017). An important difference between AGLA/PROCAM and SCORE is the outcome variable estimate, which is myocardial infarction for AGLA/PROCAM (CHD) and which is myocardial infarction, stroke and coronary revascularisation for SCORE (CVD).…”
Section: Discussionmentioning
confidence: 89%